Pengaruh Pendapatan Asli Daerah, Ukuran Pemerintah Daerah, Tingkat Ketergantungan Pemerintah Daerah Terhadap Tingkat Pengungkapan Laporan Keuangan Pemerintah Daerah - Edo Anggara; Charoline Cheisviyanny (Universitas Negeri Padang, 2020)
This study aims to empirically show the effect of of original local government revenue on local government scope, the dependence level of local government and audit findings against financial statements disclosure of local government. The sample selection uses the total sampling method. Original local government revenue is measured by using the natural logarithm of regional revenue, local government scope is measured by total local government assets in LKPD, dependency level of local government is measured by fund transfers divided by total revenue, audit findings are measured from the results of audits of the Indonesian Supreme Audit Institution on the internal control system of government (BPK). This findings show that the level of local government dependency has positive effect on the level of financial statements disclosure in local government. The findings with the sig value of 0,000 <0.05, and the calculated value of 3.785> tt table 2.006, it can be concluded that the H3 Hypothesis Accepted, and this study can contribute empirically by 28.91%. Meanwhile, the original local government revenue on local government scope variable, size of local government and audit findings do not affect the level of financial statement disclosure. The suggestions for further research are expected to improve the number of research samples and observation year. Moreover, the other variables can be used to measure the level of disclosure , and the data analysis techniques is qualitative using interview method to obtain information about disclosure of financial statement